Functional and transcriptomic analysis of extracellular vesicles identifies calprotectin as a new prognostic marker in peripheral arterial disease (PAD). Issue 1 (19th February 2020) - Saenz‐Pipaon, Goren; San Martín, Patxi; Planell, Núria; Maillo, Alberto; Ravassa, Susana; Vilas‐Zornoza, Amaia; Martinez‐Aguilar, Esther; Rodriguez, José Antonio; Alameda, Daniel; Lara‐Astiaso, David; Prosper, Felipe; Paramo, José Antonio; et al.
ABSTRACT: Peripheral arterial disease (PAD) is associated with a high risk of cardiovascular events and death and is postulated to be a critical socioeconomic cost in the future. Extracellular vesicles (EVs) have emerged as potential candidates for new biomarker discovery related to their protein and nucleic acid cargo. In search of new prognostic and therapeutic targets in PAD, we determined the prothrombotic activity, the cellular origin and the transcriptomic profile of circulating EVs. This prospective study included control and PAD patients. Coagulation time (Procoag‐PPL kit), EVs cellular origin and phosphatidylserine exposure were determined by flow cytometry in platelet‐free plasma (n = 45 PAD). Transcriptomic profiles of medium/large EVs were generated using the MARS‐Seq RNA‐Seq protocol (n = 12/group). The serum concentration of the differentially expressed gene S100A9, in serum calprotectin (S100A8/A9), was validated by ELISA in control (n = 100) and PAD patients (n = 317). S100A9 was also determined in EVs and tissues of human atherosclerotic plaques (n = 3). Circulating EVs of PAD patients were mainly of platelet origin, predominantly Annexin V positive and were associated with the procoagulant activity of platelet‐free plasma. Transcriptomic analysis of EVs identified 15 differentially expressed genes. Among them, serum calprotectin was elevated in PAD patients ( p < 0.05) and associated with increased amputation risk before and after covariate adjustment (mean follow‐up 3.6 years, p < 0.01). The combination of calprotectin with hs‐CRP in the multivariate analysis further improved risk stratification ( p < 0.01). Furthermore, S100A9 was also expressed in femoral plaque derived EVs and tissues. In summary, we found that PAD patients release EVs, mainly of platelet origin, highly positive for AnnexinV and rich in transcripts related to platelet biology and immune responses. Amputation risk prediction improved with calprotectin and was significantly higher when combined with hs‐CRP. Our results suggest that EVs can be a promising component of liquid biopsy to identify the molecular signature of PAD patients.